2003
DOI: 10.1038/sj.ejcn.1601678
|View full text |Cite
|
Sign up to set email alerts
|

Beer and obesity: a cross-sectional study

Abstract: Objective: There is a common notion that beer drinkers are, on average, more 'obese' than either nondrinkers or drinkers of wine or spirits. This is reflected, for example, by the expression 'beer belly'. However, the few studies on the association between consumption of beer and abdominal obesity produced inconsistent results. We examined the relation between beer intake and waist-hip ratio (WHR) and body mass index (BMI) in a beer-drinking population. Design: A cross-sectional study. Settings: General popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 10 publications
3
29
0
2
Order By: Relevance
“…The directions of the relations between alcohol consumption in average amount per week and overweight are not Risk factors for overweight and obesity in adolescents S Croezen et al consistent in literature; positive, negative and no associations were reported (Lahti-Koski et al, 2002;Bobak et al, 2003;Wannamethee and Shaper, 2003;Suter, 2004;Yeomans, 2004). A study by Breslow and Smothers (2005) that distinguished between amount of consumed alcohol and frequency of drinking occasions in adults, reported different results for the relation between amounts of alcohol consumed with BMI and between frequencies of alcohol consumed with BMI.…”
Section: Risk Factors For Overweight and Obesity In Adolescents S Cromentioning
confidence: 59%
See 1 more Smart Citation
“…The directions of the relations between alcohol consumption in average amount per week and overweight are not Risk factors for overweight and obesity in adolescents S Croezen et al consistent in literature; positive, negative and no associations were reported (Lahti-Koski et al, 2002;Bobak et al, 2003;Wannamethee and Shaper, 2003;Suter, 2004;Yeomans, 2004). A study by Breslow and Smothers (2005) that distinguished between amount of consumed alcohol and frequency of drinking occasions in adults, reported different results for the relation between amounts of alcohol consumed with BMI and between frequencies of alcohol consumed with BMI.…”
Section: Risk Factors For Overweight and Obesity In Adolescents S Cromentioning
confidence: 59%
“…Between 1988 and 1998, the consumption of alcohol in boys (13-18 years) increased with 86% (Health council of the Netherlands, 2002;Kreijl, 2004). It is relatively unclear whether alcohol consumption is a risk factor for overweight, as studies have equally reported a positive, negative or no association (Westerterp, 1999;Lahti-Koski et al, 2002;Bobak et al, 2003;Wannamethee and Shaper, 2003;Suter, 2004;Yeomans, 2004). In addition, no studies were found describing the relations between alcohol consumption and overweight in adolescents.…”
Section: Introductionmentioning
confidence: 94%
“…It is believed that beer consumption is associated with increased waist circumference (WC), particularly in men-a phenomenon popularly referred to as 'beer belly'. This belief might have found support by cross-sectional research, reporting abdominal obesity as being associated with beer consumption (Slattery et al, 1992;Duncan et al, 1995;Dallongeville et al, 1998;Bobak et al, 2003;Wannamethee et al, 2005). In contrast, prospective studies have been rather inconsistent, reporting positive associations (Vadstrup et al, 2003;Vernay et al, 2004), no associations (Halkjaer et al, 2004;Koppes et al, 2005) or even marginally negative associations among men (Halkjaer et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
“…In cross-sectional studies, beer intake was either not related to WHR or BMI (Bobak et al, 2003;Lukasiewicz et al, 2005), or it was related (632) 2281 (679) 2262 (675) 2269 (648) 2230 (617) 2228 (608) 2284 (630) 2364 (639) 2494 (674) Total fat intake (mean, s. (520) 1824 (525) 1863 (536) 1874 (521) 1881 (506) 1868 (515) 1862 (539) 1907 (580) Total fat intake (mean, s. Lifetime alcohol and abdominal adiposity MM Bergmann et al in both genders and all ethnic groups (Slattery et al, 1992;Wannamethee et al, 2005). However, comparable to our study, abdominal adiposity was also seen for other types of beverage, independent from BMI (Dallongeville et al, 1998).…”
Section: Discussionmentioning
confidence: 99%